Features of proverbs and sayings in M. Kashgari’s Diwani Luhat it-Turk - Kossybayev М.; Adilov М.; Yendibay М. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2024)
Proverbs and sayings are the key to the knowledge of culture.They play a great force involved in the formation of spiritual and material culture, a monument of the culture of the people, a mirror of the life of the people, folklore, revealing the artistic thought of the people. Wise words that sound rational and short were formed from the ancient Turkic language, this is a phenomenon born of centuries of human life experience. There is reason to believe that the final opinions are deeply significant instructive words that have become proverbs and sayings among the people that have come down from ancient times to the present day. A number of medieval Turkic written monuments, for example, those written by M. Kashgari, J. Balasagun, and A. Yugineki, are full of proverbs and sayings. The study of proverbs and sayings in the legacy of the Middle Ages provides an opportunity to study the Turkic worldview. Recognizing the new, learning the old, studying the heritage left by the ancestors, using it for the benefit of the Kazakh people is the main requirement of today. The article analyzes the features of proverbs and sayings in M. Kashgari’s work “Divani lugat it-Turk”.